Post-caldera monogenetic volcanism at Deception Island, Antarctica: morphometric analysis and implications for hazard assessment - Pedrazzi, Dario; Kereszturi, G.; Lobo, Agustín; Geyer, Adelina; Calle, Janina (2019)
27th IUGG General Assembly in Montréal, Québec, Canada, July 8-18, 2019 Deception Island (DI), one of the most active volcanoes in Antarctica, had more than 20 monogenetic eruptions during the Holocene. The latest episodes in 1967, 1969 and 1970 destroyed, or severely damaged, the scientific bases that operated on the island. It is not possible to rule out the possibility of a future eruption in the future and in order to evaluate the eruptive recurrence is important to know the ages of most of the post-caldera edifices. This is one of the main problems at DI, due to the lack of data. The objective of this study is to carry out the morphometric analysis of the volcanic edifices and craters recognisable on the island, to establish a correlation between morphometry and the age of the post-caldera monogenetic landforms. This methodology has been used since the 70¿s to analyse mafic monogenetic volcanoes but it has not been fully developed until recently. One of the main peculiarity of DI is that these structures were probably affected by post-eruptive volcanic or erosive processes and that most of the volcanic edifices are tuff cones, due to magma-water interaction. The results obtained will allow improving the estimation of the eruptive recurrence of the island and, in turn, fundamental point for the advising of the volcanic hazard. This research was supported by the MICINN grant CTM2011- 13578-E and partially funded by the POSVOLDEC project (CTM2016-79617-P) (AEI/FEDER-UE). A.G. is grateful for her Ramón y Cajal contract (RYC-2012-11024). D.P. is grateful for his Juan de la Cierva Contract (IJCI-2016-30482).